2007
DOI: 10.1007/s00251-006-0179-1
|View full text |Cite
|
Sign up to set email alerts
|

A gene family of putative immune recognition molecules in the hydroid Hydractinia

Abstract: Animal taxa display a wide array of immune-type receptors that differ in their specificities, diversity, and mode of evolution. These molecules ensure effective recognition of potential pathogens for subsequent neutralization and clearance. We have characterized a family of putative immune recognition molecules in the colonial hydroid Hydractinia symbiolongicarpus. A complementary DNA fragment with high similarity to the sea urchin L: -rhamnose-binding lectin was isolated and used to screen 9.5 genome equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 51 publications
0
30
0
1
Order By: Relevance
“…Cnidarians distinguish precisely between self and non-self attributes and react specifically to an array of allogeneic challenges (Grosberg, 1988;Leddy and Green, 1991;Rinkevich et al, 1994;Cadavid et al, 2004;Schwarz et al, 2007;Mydlarz et al, 2008;Palmer et al, 2008;Dunn, 2009). This is performed by allorecognition systems that demonstrate all of the variety of features found in the complex structure of the vertebrate immune systems (Rinkevich, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cnidarians distinguish precisely between self and non-self attributes and react specifically to an array of allogeneic challenges (Grosberg, 1988;Leddy and Green, 1991;Rinkevich et al, 1994;Cadavid et al, 2004;Schwarz et al, 2007;Mydlarz et al, 2008;Palmer et al, 2008;Dunn, 2009). This is performed by allorecognition systems that demonstrate all of the variety of features found in the complex structure of the vertebrate immune systems (Rinkevich, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides ample evidence for the crucial role of invertebrates' innate immunity in manifesting these highly specified arrays of effector mechanisms (Loker et al, 2004) and the importance of high polymorphism for their efficient maintenance and expression (Rinkevich, 2004;Cadavid et al, 2004). While allorecognition is one of the major characteristics of invertebrate immunity, its qualities and the events expressed morphologically by the effector arms vary fundamentally between different taxa, although all share the hallmark nature of precise discriminatory capability between 'self' and 'non-self', even between closely related conspecifics (Grosberg, 1988;Leddy and Green, 1991;Rinkevich, 1996;Rinkevich, 1999;Schwarz et al, 2007). Historecognition of 'self' versus 'non-self', however, may represent two separate avenues for immunity, either by detecting the presence or absence of attributes that define self or by detecting the presence or absence of non-self attributes (Neigel, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although first pioneering genetic analyses date back several decades (Hauenschild, 1954(Hauenschild, , 1956 in H. echinata) only extensive positional cloning of two allorecognition loci alr1 and alr2 in H. symbiolongicarpus (Mokady and Buss 1996;Cadavid et al, 2004;Schwarz et al, 2007;Nicotra et al, 2009;Rosa et al, 2010;Rosengarten et al, 2011;Rosengarten and Nicotra, 2011) eventually provided evidence for the involvement of molecules belonging to the immunoglobulin superfamily. In 2009 a first gene was identified that encodes a putative transmembrane receptor expressed in all tissues capable of allorecognition.…”
Section: Regulators Of Allorecognition In Hydractiniamentioning
confidence: 99%
“…BLAST analysis showed that CEL is similar to Rhamnospondin from the congeneric hydroid, Hydractinia symbiolongicarpus (Schwarz et al, 2007), and to some predicted proteins from the sea anemone, Nematostella vectensis, and the freshwater polyp, Hydra spp. CEL also displayed similarity to numerous TSPcontaining proteins, such as hemicentins, which are not lectins, and to some lectins that lack TSP domains, such as RBL (Hosono et al, 1999).…”
mentioning
confidence: 99%